2000
DOI: 10.3171/jns.2000.93.1.0033
|View full text |Cite
|
Sign up to set email alerts
|

Venous ophthalmodynamometry: a noninvasive method for assessment of intracranial pressure

Abstract: Ophthalmodynamometry can be relevant for momentary assessment and is not suitable for continuous monitoring. However, this technique can easily be repeated and may be used whenever increased ICP is suspected in a patient suffering from hydrocephalus, brain tumors, or head injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 3 publications
5
43
0
6
Order By: Relevance
“…11,12) Papilledema may also be caused by venous congestion of the optic nerve due to impaired sinus drainage. 1,[3][4][5] Generalized intraocular venous congestion and cavernous sinus thrombosis (or stenosis) …”
Section: Discussionmentioning
confidence: 99%
“…11,12) Papilledema may also be caused by venous congestion of the optic nerve due to impaired sinus drainage. 1,[3][4][5] Generalized intraocular venous congestion and cavernous sinus thrombosis (or stenosis) …”
Section: Discussionmentioning
confidence: 99%
“…2 Vein pulsation pressure is linearly associated with intracranial pressure, and the presence or absence of spontaneous venous pulsation is a useful clinical sign for the assessment of elevated intracranial pressure. 12 Vein pulsation pressure can be measured in only 2% to 5% of normal subjects and 46% of glaucoma subjects by ophthalmodynamometry, although in a greater proportion of subjects with raised intracranial pressure. 7,13 It is a subjective measurement, with the ''minimal detectable pulsation'' threshold varying between observers.…”
mentioning
confidence: 99%
“…The study may add to the clinical application of modern ophthalmodynamometry as already demonstrated in previous investigations on glaucoma, measurement of intracerebral pressure, assessment of tissue pressure in the orbit in patients with endocrine orbitopathy, ischaemic ophthalmopathy and retinal vein occlusions. [4][5][6][7][8][9][10][11][12] …”
Section: Resultsmentioning
confidence: 99%